How Suriname came to its own green revolution : a study of change in smallholder farming in the Nickerie District, 1900-1986 - Sital, J. T. (Wageningen University. Development Economics Group WageningenNL, 2002)
Presents a historical as well as a farm-economic analysis of a period of almost one hundred years, of family rice farming in the rice bowl of Suriname i. e. the Nickerie District.